2003
DOI: 10.1007/bf02703336
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic cases of male infertility from a region in India show low incidence of Y-chromosome microdeletion

Abstract: Chromosomal and Y-chromosomal microdeletion analysis has been done in cases of idiopathic infertility with the objective of evaluating the frequency of chromosomal and molecular anomaly as the causal factor of infertility. Barring a few cases of Klinefelter syndrome (XXY or XY/XXY mosaics), no chromosomal anomaly was encountered. Y-microdeletion was analysed by PCR-screening of STSs from different regions of the AZF (AZFa, AZFb, AZFc) on the long arm of the Y, as well as by using DNA probes of the genes RBM, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
6
31
1
Order By: Relevance
“…The reason is probably the strict selection criteria applied in our study as well as geographic and ethnic differences. Within India, studies have been carried out in different regions, which showed a frequency between 5% and 9.5% (21)(22)(23). The selection criteria in these were also different from the criteria used in our study, the number of STSs used were variable.…”
Section: Discussionmentioning
confidence: 68%
“…The reason is probably the strict selection criteria applied in our study as well as geographic and ethnic differences. Within India, studies have been carried out in different regions, which showed a frequency between 5% and 9.5% (21)(22)(23). The selection criteria in these were also different from the criteria used in our study, the number of STSs used were variable.…”
Section: Discussionmentioning
confidence: 68%
“…However, in the data compiled herein there are several instances of isolated STS deletions, in most studies only single STS PCR strategy has been used. Except for one study [3], none of the deletions identified using the unconventional markers have been validated by Southern blotting or independent PCR technique. Thus there is a possibility that some of the deletions reported herein may be false positives.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of AZF microdeletions in azoospermic males varies considerably across studies and populations (3-55%) (Foresta et al, 1998;Ambasudhan et al, 2003;Vogt et al, 2004;Behulova et al, 2011). Such a wide range of variation is likely not only due to the effects of geography, ethnicity, and environmental factors, but also to the choice of inclusion criteria and the number of STSs used in different laboratories (Ambasudhan et al, 2003;Mitra et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Microdeletions of azoospermia factor (AZF) loci on the long arm of the Y chromosome are a major cause of male infertility in populations throughout the world (Mitra et al, 2006;Li et al, 2008;Wang et al, 2010). As early as 1976, Tiepolo and Zuffardi followed by other authors postulated that genes and gene families located on locus 11 of the Y chromosome long arm (Yq11) were associated with male germ cell development (Ambasudhan et al, 2003;Wang et al, 2010;Behulova et al, 2011). It was later found that microdeletions of four subregions of the AZF region (AZFa, AZFb, AZFc, and AZFd) led to various types of spermatogenesis impairments, from teratozoospermia to infertility, with different population distributions depending on their Y haplogroup profile (Li et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation